(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
Value for Money (VFM) or performance management audits have become essential tools in both public and private sectors, ensuring that resources are utilized economically, efficiently, and effectively. This article explores the principles, methodologies, impacts, and challenges of VFM audits, drawing on empirical studies and international best practices. The analysis includes real-world examples, tables, and references to Scopus-indexed literature.